Perbatasan, Nelayan Dan Kemiskinan; Konstruk Kemiskinan Pada Wilayah Perbatasan Indonesia-Filipina - Sunandar Macpal (Universitas Negeri Medan, 2021)
This paper intends to explain how the construct of poverty occurs in coastal communities and small islands on the Indonesia-Philippines border. This paper is a literature review that uses social exclusion as a basis for building discourse. Sangihe Regency is a coastal area located in Indonesia — the Philippines border region. As a coastal area, many people earn a living as fishermen. Poverty that occurs in the Sangihe region is a structural (state) consequence that makes the Sangihe region become a border. The policy to modernize fishermen as a step to reduce poverty actually eliminates many local traditions, including the duality of livelihoods. In addition, modernizing has also had impact on the loss of culture at the level of knowledge and language.